Disentangling the Effect of Seasonal Dynamics on Meiobenthic Community Structure From River Matla of Sundarbans Estuarine System, India - Ghosh, Moumita; Mandal, Sumit (Frontiers in Marine Science, 2021)
In estuarine sediment, meiobenthos serve as an excellent candidate to perform a range of ecosystem services. However, even though the taxonomic sufficiency of meiobenthos in detecting spatiotemporal gradients is well recognized, very little is known about their functional attributes in response to environmental descriptors. To bridge this knowledge gap, the taxonomic structure and trait-based functional diversity patterns of meiobenthic assemblage, focusing on nematode species composition, were assessed for the first time from the unexplored central sector of Sundarbans Estuarine System (SES). Sediment samples were collected seasonally (monsoon, winter, spring, and summer) selecting a total of eight stations across River Matla (the widest and longest river of SES). Distinct seasonal successional patterns had been observed in meiobenthic abundance modulated by seasonal alteration in the sedimentary environment (PERMANOVA, p < 0.05). Our study revealed a strong preponderance of meiobenthic density in spring (2978 ± 689.98 ind. 10 cm–2) and lowest during monsoon (405 ± 51.22 ind. 10 cm–2). A total of 11 meiobenthic taxa were identified with the dominance of nematodes. Altogether, 79 species of nematode belonging to 22 families had been identified across the entire study area and nematode assemblage was dominated by Sabatieria praedatrix, Sphaerolaimus balticus, Desmodora communis, Dorylaimopsis punctata, and Daptonema hirsutum. Principal component analysis depicted a distinct separation of seasons with reference to environmental variables. Distance-based redundancy analysis delineated that meiobenthic communities were mainly structured by organic matter, salinity, and dissolved oxygen concentration. Biological trait analyses of nematode assemblages were applied to gather the ecological information based on morphological and ecological characteristics. The most common morphotypes were slender body shape, clavate tail shape, striated cuticle pattern, and non-selective deposit feeders with colonizing abilities of 2–3 (c–p score in a scale from 1 to 5). Results from BIO-ENV showed that sediment organic matter and dissolved oxygen played overriding roles in shaping the functional compositions of nematodes. Thus, the characterization of meiobenthos and nematode assemblages in the context of taxonomic as well as functional attributes represents a first step toward building of baseline data which could help to evaluate the ecological status of SES and direct future research priorities concurrently.